Total hemosiderin score in the tracheal wash fluid when assessing exercise-induced pulmonary hemorrhage in thoroughbred racehorses - Cascardo, Bianca (2025)
Exercise-induced pulmonary hemorrhage (EIPH) is one of the main respiratory conditionsthat requires clinical follow-up in equine sports medicine. Post exertional airway endoscopy is thereference standard for diagnosing EIPH, however the severity score is based on the amount of bloodthat ascend the tracheobronchial tree, which might not accurately reflect lung injury. Although thetotal hemosiderin score (THS) in the bronchoalveolar lavage fluid (BALF) has been shown to havea good sensitivity to diagnose EIPH, racehorse owners and trainers are often reluctant to allowthis procedure. The use of the tracheal wash fluid (TWF) to assess EIPH through THS has beendemonstrated as an alternative diagnostic approach. The present study evaluated the sensitivity andspecificity of THS when applied in TWF samples of Thoroughbred racehorses to establish diagnosticcut-off values. Horses were grouped according to their athletic development, EIPH endoscopic grade,and use of furosemide. Differential cell counts and mean THS by group and by endoscopic gradewere compared by the Median Test. Sensitivity and specificity were assessed with a contingency table,and the receiver operating characteristic curve was used to define optimal cut-off values. The cut-offvalues 30, 138, and 246 were established to interpret THS results according to clinical history. A THSscore of ≥246 can be interpreted as evidence of past bleeding and provides unequivocal confirmationof EIPH in healthy animals. This study demonstrates how defining appropriate cut-off values for THSin TWF samples can aid in the diagnosis and monitoring of EIPH in clinical practice.